1998
DOI: 10.1152/ajplung.1998.274.5.l694
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of lung liquid clearance by isoproterenol in rat lungs

Abstract: β-Adrenergic agonists have been reported to increase lung liquid clearance by stimulating active Na+ transport across the alveolar epithelium. We studied mechanisms by which β-adrenergic isoproterenol (Iso) increases lung liquid clearance in isolated perfused fluid-filled rat lungs. Iso perfused through the pulmonary circulation at concentrations of 10−4 to 10−8 M increased lung liquid clearance compared with that of control lungs ( P < 0.01). The increase in lung liquid clearance was inhibited by the β-ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
72
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(87 citation statements)
references
References 27 publications
14
72
1
Order By: Relevance
“…Treatment of rats with insulin increases AFR to a level similar to that we have previously reported for -adrenergic receptor agonists (Saldias et al, 1998;Saldias et al, 2002;Saldias et al, 2000;Sznajder et al, 2002). In some experiments, rats were pretreated with the -receptor antagonist propranolol to prevent a potential increase in AFR due to hypoglycemia-induced catecholamine release.…”
Section: Discussionsupporting
confidence: 69%
“…Treatment of rats with insulin increases AFR to a level similar to that we have previously reported for -adrenergic receptor agonists (Saldias et al, 1998;Saldias et al, 2002;Saldias et al, 2000;Sznajder et al, 2002). In some experiments, rats were pretreated with the -receptor antagonist propranolol to prevent a potential increase in AFR due to hypoglycemia-induced catecholamine release.…”
Section: Discussionsupporting
confidence: 69%
“…Scale bars: 10m and 4m (magnified images). (Bertorello et al, 1999;Lecuona et al, 2003;Saldias et al, 1998). Recruitment of Na + /K + -ATPase-containing vesicles into the plasma membrane is known to involve both microtubules and the actin network (Bertorello et al, 2003;Bertorello et al, 1999;Saldias et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In the lungs, the Na + /K + -ATPase located at the basolateral plasma membrane drives the vectorial Na + transport across the alveolar epithelium necessary to keep the alveoli free of edema (Mutlu and Sznajder, 2005;Sznajder et al, 2002). Alveolar fluid reabsorption is increased after stimulation of Na + /K + -ATPase activity by G-protein-coupledreceptor (GPCR) agonists that activate the second messenger cAMP (Frank et al, 2000;Litvan et al, 2006;Saldias et al, 1998). cAMP increases the Na + /K + -ATPase function in alveolar epithelial cells by promoting its recruitment from intracellular vesicle pools into the plasma membrane (Bertorello et al, 1999;Lecuona et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, inconsistent with rat lungs, b2-adrenergic agonists did not increase alveolar fluid clearance in rabbit and guinea pig lungs (12, 13). Interestingly, isoproterenol increased alveolar fluid clearance via b 1-adrenoceptors in guinea pig lungs (13), whereas isoproterenol increased alveolar fluid clearance via b 2-adrenoceptors in rat lungs (14). Recently, we reported that denopamine, a selective b1-adrenergic agonist, increased alveolar fluid clearance in normal rat and guinea pig lungs (15).…”
Section: Abstract: Pulmonary Edema Lung Injury Sodium Transport Almentioning
confidence: 99%